Stakeholder influence on corporate reporting: An exploration of the interaction between WWF-Australia and the Australian minerals industry - Deegan, Craig; Blomquist, Christopher (Accounting, Organizations and Society, 2006)
This paper explores the influence an initiative of WWF-Australia had on the environmental reporting practices of the Australian minerals industry. In 1999, WWF-Australia produced a report that evaluated the environmental reports of companies that were signatories to the Australian Minerals Industry Code for Environmental Management. The evidence provided in this paper suggests that the WWF’s initiative influenced revisions to the industry code, as well as the reporting behaviour of individual mining companies. The study contributes to the limited amount of research that has been conducted with regard to the influence that lobby groups have on corporate disclosure policies.